PEMBERDAYAAN IBU RUMAH TANGGA PELAKU USAHA IKM MELALUI INOVASI PENGOLAHAN UMBI-UMBIAN MENJADI KERIPIK - Rizal, Abdul; Adryani Moento, Paul; Adrianus, Adrianus; Mekiuw, Yosehi; Anwar, Anwar; Yusuf, Mani (Universitas Halu Oleo, 2023)
Andaito Village is a village in the Muting District, Merauke Regency, South Papua Province. In this village, the majority of the population earn their living as farmers. The agricultural business being developed is tubers which are then processed into chips on a home industrial scale. The chips business was developed by housewives, although the processing is still traditional, relying on cassava choppers made of wood. One of the reasons is that people have minimal business capital and knowledge of innovation. Thus, through this service activity, the implementing team will provide solutions to problems faced by partners both in terms of technology, business management and marketing of results. This service activity is carried out using an individual counseling method, namely visiting the homes of business owners to provide understanding and knowledge related to technological innovation and product marketing. The objectives of implementing this program are (a) Increasing knowledge about SME businesses, (b) Increasing knowledge of housewives about effective marketing systems, (c) Increasing skills regarding traditional processing systems to modern ones. The output targets adapted to this activity plan include physical and non-physical products, namely publication of ISSN journals, print/online media publications, increasing business competitiveness, application of mechanization science and technology, improving the economy, improving values in society, increasing discipline and participation.